Rethinking Trauma and Gender Dynamics in Nigeria Films: A Comparative Analysis of Damage and Mr. and Mrs - Olanireti O. Falade; Kareem K. Ganiyu; Babatunde Covenant Olugbenga (Britain International for Academic Research (BIAR) Publisher, 2025)
The subjugation of women within certain aspects of Nigerian culture is a significant concern that necessitates comprehensive efforts across multiple levels, including individual, relational, community, and societal interventions. Recently, both organizations and filmmakers have sought to highlight various societal issues that persistently traumatize women and children in the country. This research, therefore, offers an in-depth comparative analysis of trauma and gender dynamics as portrayed in the films Damage and Mr. and Mrs. Utilizing a qualitative methodology that combines content analysis of the selected films with Johan Galtung’s theory of structural violence, the research posits that the intricate depictions of violence in both films can be understood through their societal and cultural contexts. By examining the characters’ responses to challenges and conflicts, the study evaluates how effectively these films confront and dismantle traditional gender norms, fostering essential discourse on trauma, resilience, and societal transformation. A crucial aspect of the research involves examining audience attitudes and behaviors related to gender-based violence (GBV), assessed before, during, and after the viewing experience. This component provides significant insights into viewers’ perceptions, emotional reactions, and their understanding of GBV and its implications. Moreover, the study engages with crucial questions about establishing a more equitable community, where the dynamics between men and women move beyond the oppressive ‘master and slave’ paradigm. By delving into these themes, this research aims to enhance the growing body of literature that investigates the media’s critical role in shaping public perceptions and narratives surrounding gender-based violence